Oxygen Evolution Electrode

A titanium electrode with a ruthenium-tin-polyvalent metal oxide catalyst layer and optional intermediate and barrier layers addresses durability issues, ensuring high conductivity and long-term operation in acidic electrolytes.

JP7621071B2Active Publication Date: 2025-01-24DE NORA PERMELEC LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020123597
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-20
Publication Date
2025-01-24
Estimated Expiration
2040-07-20

AI Technical Summary

Technical Problem

The durability of catalyst layers containing ruthenium in titanium electrodes for oxygen generation is compromised in acidic electrolytes, limiting their use in long-term electrolysis processes.

Method used

A titanium-based electrode with a catalyst layer composed of mixed metal oxides containing ruthenium, tin, and polyvalent metals, with specific mole percentages, and optionally an intermediate and barrier layer, to enhance conductivity and durability.

Benefits of technology

The electrode maintains high conductivity and prevents catalyst component consumption, enabling long-term electrolysis even in acidic conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621071000005
    Figure 0007621071000005
  • Figure 0007621071000006
    Figure 0007621071000006
  • Figure 0007621071000007
    Figure 0007621071000007
Patent Text Reader

Abstract

To provide an electrode for generating oxygen of high electric conductivity, hardly consuming a catalyst component even when electrolyzing an acidic electrolytic liquid, capable of carrying out electrolysis for a long time, and comprising a catalyst layer of excellent durability.SOLUTION: An electrode 10 for generating oxygen comprises a substrate 2 formed of titanium or a titanium alloy, and a catalyst layer 4 formed of a mixed metal oxide and disposed on the substrate 2. The catalyst layer 4 satisfies at least one of the following conditions (1) and (2). The condition (1): Ruthenium, tin, and a polyvalent element having a valence of three or higher (excluding a valence of four) are contained therein. The condition (2): Ruthenium and tin are contained therein with the content of ruthenium being 40 mole% or more relative to the total content of ruthenium and tin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode for oxygen evolution. [Background technology]

[0002] In the process of electrowinning of nonferrous metals such as copper, nickel, and zinc, sulfuric acid or strong acid electrolyte is generally used. And, as the counter electrode, an oxygen generating electrode that causes oxygen generating reaction is used as the anode. Titanium electrodes with a coating layer containing mixed metal oxide (MMO) as a catalyst layer on the surface have lower overvoltage characteristics for oxygen generating reaction, and therefore have been proposed as an alternative anode for electrowinning process that can reduce energy consumption and can replace lead alloy electrodes that have been conventionally used as oxygen generating electrodes.

[0003] The mixed metal oxide for forming the catalytic layer is usually a composite oxide of iridium (Ir) as an active element and valve metals such as tantalum (Ta), tin (Sn), titanium (Ti), zirconium (Zr), and niobium (Nb) as binder elements. As an electrode using such a composite oxide, a titanium electrode for oxygen generation provided with a catalytic layer containing IrO2-Ta2O5 has been proposed (Non-Patent Document 1). However, since iridium is one of the most expensive and rare elements, there is a problem that it is not economically versatile as a material for forming the catalytic layer of the anode for electrowinning process.

[0004] In contrast, it is known that ruthenium (Ru) oxide (RuO2), which is cheaper than iridium, exhibits high electrocatalytic activity in the oxygen evolution reaction (OER), and is attracting attention as an alternative to iridium. For example, a titanium electrode with a catalytic layer containing RuO2-Ta2O5, a composite oxide that does not use iridium, has been proposed (Non-Patent Document 2). [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Journal of Applied Electrochemistry,1991,21,p.335-345 [Non-Patent Document 2] Proceedings of Copper 2016 (abstract collection), p.2145-2152 Summary of the Invention [Problem to be solved by the invention]

[0006] However, when ruthenium is used as an active element constituting the catalytic layer of a titanium electrode for oxygen generation, there is a problem that the durability of the catalytic layer is reduced, and therefore, an oxygen generation electrode provided with a catalytic layer containing ruthenium as an active element has a problem that it is difficult to apply the electrode to long-term electrolysis over, for example, several years.

[0007] The present invention has been made in consideration of the problems associated with the conventional techniques, and an object of the present invention is to provide an oxygen generating electrode provided with a catalyst layer having high electrical conductivity, in which the catalyst components are not easily consumed even when an acidic electrolyte is electrolyzed, and which is capable of electrolysis for a long period of time and has excellent durability. [Means for solving the problem]

[0008] That is, according to the present invention, the following oxygen evolution electrode is provided. [1] An electrode for oxygen generation comprising: a substrate made of titanium or a titanium alloy; and a catalytic layer made of a mixed metal oxide disposed on the substrate, wherein the catalytic layer satisfies at least one of the following conditions (1) and (2): Condition (1): The material contains ruthenium, tin, and a polyvalent metal element having a valence of three or more (excluding tetravalent). Condition (2): Ruthenium and tin are contained, and the content of ruthenium is 40 mol % or more based on the total content of ruthenium and tin. [2] The oxygen generation electrode according to [1], wherein the catalytic layer satisfies the condition (1), and the content of the polyvalent metal element in the catalytic layer is 2 to 20 mol % based on the total metal elements in the catalytic layer. [3] The electrode for oxygen evolution according to [1] or [2], wherein the polyvalent metal element is at least one selected from the group consisting of bismuth, tantalum, lanthanum, niobium, and molybdenum. [4] The oxygen generation electrode according to any one of [1] to [3], wherein the catalytic layer satisfies the condition (1) and the content of ruthenium in the catalytic layer is 20 to 70 mol % based on the total metal elements in the catalytic layer. [5] The oxygen evolution electrode according to any one of [1] to [4], wherein the catalytic layer further contains manganese. [6] The oxygen generation electrode according to any one of [1] to [5] above, further comprising an intermediate layer disposed between the substrate and the catalyst layer. [7] The oxygen generation electrode according to any one of [1] to [6] above, further comprising a barrier layer disposed on the catalyst layer. [8] The electrode for oxygen evolution according to any one of the above [1] to [7], which is used as an anode for an electrowinning process of non-ferrous metals. Effect of the Invention

[0009] According to the present invention, it is possible to provide an oxygen generating electrode having a catalyst layer with high electrical conductivity, in which the catalyst components are not easily consumed even when an acidic electrolyte is electrolyzed, and which is capable of electrolysis for a long period of time and has excellent durability. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic diagram showing one embodiment of an oxygen evolution electrode of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing another embodiment of the oxygen evolution electrode of the present invention. [Diagram 3] FIG. 2 is a schematic view showing still another embodiment of the oxygen evolution electrode of the present invention. [Figure 4]FIG. 2 is a schematic view showing still another embodiment of the oxygen evolution electrode of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. The oxygen generating electrode of the present invention comprises a substrate made of titanium or a titanium alloy, and a catalyst layer made of a mixed metal oxide disposed on the substrate. The catalyst layer satisfies at least one of the following conditions (1) and (2). Hereinafter, the oxygen generating electrode of the present invention will be described in detail. Condition (1): The material contains ruthenium, tin, and a polyvalent metal element having a valence of three or more (excluding tetravalent). Condition (2): Ruthenium and tin are contained, and the content of ruthenium is 40 mol % or more based on the total content of ruthenium and tin.

[0012] (base material) Fig. 1 is a schematic diagram showing one embodiment of the oxygen generating electrode of the present invention. As shown in Fig. 1, the oxygen generating electrode 10 of this embodiment includes a substrate 2 and a catalyst layer 4 disposed on the substrate 2. The substrate 2 is made of titanium or a titanium alloy. The overall shape of the substrate 2 is not particularly limited and can be appropriately designed depending on the application. Examples of the overall shape of the substrate include a plate shape, a rod (column) shape, a mesh shape, and the like.

[0013] (catalyst layer) The catalyst layer 4 disposed on the substrate 2 is formed of a mixed metal oxide (FIG. 1). This mixed metal oxide is a composite oxide of multiple metal elements, and functions as a catalyst for electrolysis. The catalyst layer is a layer that satisfies at least one of the following conditions (1) and (2), and preferably satisfies both of the following conditions (1) and (2). Condition (1): The material contains ruthenium, tin, and a polyvalent metal element having a valence of three or more (excluding tetravalent). Condition (2): Ruthenium and tin are contained, and the content of ruthenium is 40 mol % or more based on the total content of ruthenium and tin.

[0014] The thickness of the catalyst layer is not particularly limited and can be set arbitrarily, for example, to 1 to 10 μm.

[0015] [Condition (1)] The catalyst layer contains ruthenium (Ru), tin (Sn), and a trivalent or higher (except for tetravalent) polyvalent metal element (hereinafter, also simply referred to as "polyvalent metal element"). That is, the catalyst layer is formed of ruthenium as an active element, tin as a binder element, and a mixed metal oxide that is a composite oxide of the above polyvalent metal elements. In addition to ruthenium and tin, which are tetravalent metal elements, polyvalent metal elements having a different valence from these tetravalent metal elements are allowed to coexist in the catalyst layer, making it possible to increase the electrical conductivity and to obtain an oxygen generating electrode with a lower electrode potential. In addition, by containing a polyvalent metal element, the catalyst components (especially ruthenium, which is an active element) are less likely to be consumed even when electrolysis is performed under acidic conditions such as sulfuric acid acid, and a catalyst layer with excellent durability can be obtained. In addition, the valence of a metal element in this specification means the valence (oxidation number) of a metal element that can exist in the most stable state.

[0016] Examples of polyvalent metal elements include bismuth (Bi), tantalum (Ta), lanthanum (La), niobium (Nb), and molybdenum (Mo). Among these, bismuth, tantalum, lanthanum, and niobium are preferred, and bismuth is more preferred. These polyvalent metal elements can be used alone or in combination of two or more.

[0017] When the catalyst layer satisfies the condition (1), the content of the polyvalent metal element in the catalyst layer is preferably 2 to 20 mol%, more preferably 3.5 to 15 mol%, and particularly preferably 4 to 12 mol%, based on the total metal elements in the catalyst layer. By setting the content of the polyvalent metal element in the catalyst layer within the above range, it is possible to further increase the electrical conductivity and further improve the durability of the catalyst layer. If the content of the polyvalent metal element in the catalyst layer is too small, the effect obtained by including the polyvalent metal element may be somewhat insufficient. On the other hand, if the content of the polyvalent metal element in the catalyst layer is too large, the content of the active element ruthenium and the binder element tin is relatively decreased, so that the catalytic activity may be somewhat insufficient. The type and content of the metal element in each layer including the catalyst layer can be measured and calculated by an analysis method such as X-ray fluorescence (XRF) analysis.

[0018] When the catalytic layer satisfies the condition (1), the content of ruthenium in the catalytic layer is preferably 20 to 70 mol%, more preferably 25 to 66 mol%, and particularly preferably 30 to 55 mol%, based on the total metal elements in the catalytic layer. By setting the content of ruthenium in the catalytic layer within the above range, higher catalytic activity can be obtained. If the content of ruthenium in the catalytic layer is too low, the catalytic activity may be slightly insufficient. On the other hand, if the content of ruthenium in the catalytic layer is too high, the ruthenium component is likely to aggregate. In addition, the proportion of ruthenium that does not effectively contribute to the electrolytic reaction increases relative to the coating amount, and the proportion of the binder component decreases, which may result in a decrease in durability.

[0019] [Condition (2)] The catalyst layer contains ruthenium (Ru) and tin (Sn), and the content of ruthenium is 40 mol% or more based on the total content of ruthenium and tin. That is, the catalyst layer is formed of a mixed metal oxide, which is a composite oxide of ruthenium as an active element and tin as a binder element. The catalyst layer is preferably formed of a mixed metal oxide, which is a composite oxide containing substantially only ruthenium and tin as metal elements. By setting the content of ruthenium to 40 mol% or more, preferably 43 mol% or more, and more preferably 45 mol% or more based on the total content of ruthenium and tin, it is possible to increase the electrical conductivity, and an oxygen generating electrode with a lower electrode potential can be obtained. Furthermore, by setting the content of ruthenium to the above range, the catalyst components (especially ruthenium as an active element) are less likely to be consumed even when electrolysis is performed under acidic conditions such as sulfuric acid acid, and the catalyst layer has excellent durability.

[0020] [Other metallic elements] The catalyst layer may further contain metal elements other than ruthenium and tin (other metal elements). By further containing other metal elements in the catalyst layer, it is possible to make the other metal elements act as semi-active components in the electrolytic reaction. Examples of other metal elements include manganese (Mn). That is, it is preferable that the catalyst layer further contains manganese.

[0021] When other metal elements are contained in the catalyst layer, the content of the other metal elements in the catalyst layer is usually 10 to 50 mol %, preferably 20 to 40 mol %, based on the total metal elements in the catalyst layer.

[0022] (Middle class) Fig. 2 is a schematic diagram showing another embodiment of the oxygen generating electrode of the present invention. The oxygen generating electrode 20 shown in Fig. 2 further includes an intermediate layer 6 disposed between the substrate 2 and the catalyst layer 4. By providing such an intermediate layer between the substrate and the catalyst layer, passivation of the substrate made of titanium or a titanium alloy due to electrolysis can be suppressed, and the substrate can be protected from corrosion, which is preferable. This further improves durability, making it possible to provide an oxygen generating electrode capable of electrolysis for a longer period of time.

[0023] The intermediate layer can be formed from various metals. Examples of metals for forming the intermediate layer include titanium (Ti), tantalum (Ta), tin (Sn), alloys thereof, and mixed oxides thereof. In particular, it is preferable to form the intermediate layer from an alloy of titanium and tantalum or a mixed oxide of titanium and tantalum. The thickness of the intermediate layer is not particularly limited and can be set arbitrarily. The thickness of the intermediate layer may be, for example, 0.2 to 5 μm.

[0024] (Barrier layer) 3 and 4 are schematic diagrams showing still another embodiment of the oxygen generating electrode of the present invention. The oxygen generating electrode 30 shown in FIG. 3 includes a substrate 2 and a catalyst layer 4 disposed on the substrate 2, and further includes a barrier layer 8 disposed on the catalyst layer 4. The oxygen generating electrode 40 shown in FIG. 4 includes a substrate 2 and a catalyst layer 4 disposed on the substrate 2, and further includes an intermediate layer 6 disposed between the substrate 2 and the catalyst layer 4, and a barrier layer 8 disposed on the catalyst layer 4. That is, both of the oxygen generating electrodes 30 and 40 shown in FIGS. 3 and 4 further include a barrier layer 8 disposed on the catalyst layer 4. By providing such a barrier layer (topcoat layer) on the catalyst layer, it is possible to reduce consumption of components such as ruthenium in the catalyst layer, which is preferable. In addition, it is possible to suppress the diffusion of components such as arsenic (As), antimony (Sb), and manganese (Mn), which are present in the electrolyte and can be precipitated by electrolysis, to the surface of the catalyst layer. This further improves durability, and the oxygen generating electrode can be electrolyzed for a longer period of time.

[0025] The barrier layer can be formed of, for example, the same composite oxide of a plurality of metal elements as the mixed metal oxide for forming the catalyst layer. That is, the barrier layer can be formed of a mixed metal oxide that is a composite oxide of the above-mentioned polyvalent metal elements such as bismuth in addition to ruthenium and tin. The content of the active metal element such as ruthenium in the barrier layer is preferably 0.5 to 5% based on the total metal elements in the barrier layer. In addition, the content of the binder element such as tin in the barrier layer is preferably 95 to 99.5 mol% based on the total metal elements in the barrier layer.

[0026] The thickness of the barrier layer is not particularly limited and can be set arbitrarily, for example, to 0.5 to 5 μm.

[0027] (Applications of oxygen generating electrodes) The oxygen generating electrode of the present invention has high electrical conductivity, and even when electrolyzing an acidic electrolyte such as sulfuric acid, the ruthenium in the catalyst layer is not easily consumed, and has durability suitable for long-term electrolysis. Therefore, the oxygen generating electrode of the present invention is useful, for example, as an anode (electrowinning anode) for the electrowinning process of non-ferrous metals, which is used in combination with a cathode for electrowinning of non-ferrous metals. Furthermore, when the applied current density is 10 A / m 2 It is useful as an oxygen generating electrode used in the following electrolytic processes.

[0028] (Method of manufacturing an electrode for oxygen generation) The oxygen generating electrode of the present invention can be manufactured by forming a catalyst layer made of a mixed metal oxide on a substrate. To form a catalyst layer on a substrate, for example, a coating liquid containing various metals and salts of various metals at a desired ratio is prepared, and the prepared coating liquid is applied to the surface of the substrate that has been subjected to surface treatment such as blasting or etching as necessary to form a coating layer. Then, by baking under appropriate temperature conditions, a catalyst layer made of a mixed metal oxide is formed on the substrate, and the intended oxygen generating electrode can be obtained. Note that the thickness of the catalyst layer formed and the content of metal elements can be controlled by repeating the application and baking of the coating liquid. The baking temperature is usually 450 to 550°C, preferably 480 to 520°C.

[0029] Before forming the catalyst layer, an intermediate layer can also be formed on the substrate. To form an intermediate layer on the substrate, a coating liquid containing various metals and salts of various metals at a desired ratio is first applied to the surface of the substrate to form a coating layer, as in the case of forming the catalyst layer described above. Then, the intermediate layer can be formed on the substrate by baking under appropriate temperature conditions. By repeating the application and baking of the coating liquid, the thickness of the intermediate layer formed and the content of the metal elements can be controlled. The baking temperature is usually 450 to 550°C, preferably 480 to 520°C. A catalyst layer can be formed on the formed intermediate layer according to the above-mentioned procedure.

[0030] Alternatively, the intermediate layer can be formed on the substrate as desired by ion plating, sputtering, plasma spraying or the like.

[0031] To form a barrier layer on a catalyst layer, a coating liquid containing various metals or salts of various metals is first applied to the surface of the catalyst layer to form a coating layer, as in the case of forming the catalyst layer described above. Then, the coating is baked under appropriate temperature conditions to form a barrier layer on the catalyst layer. By repeating the application and baking of the coating liquid, the thickness of the barrier layer formed and the content of metal elements can be controlled. The baking temperature is usually 450 to 550°C, preferably 480 to 520°C. EXAMPLES

[0032] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0033] <Pretreatment of substrate> A titanium mesh substrate measuring 100 mm x 100 mm x 1 mm was prepared. This mesh substrate was annealed in an air atmosphere at 590°C for 60 minutes, and then blasted with alumina (#60). It was immersed in boiling 20% ​​hydrochloric acid for 12 minutes for etching, and then washed with ion-exchanged water and dried to obtain a pretreated substrate.

[0034] <Formation of the intermediate layer> (Method (A)) The pretreated substrate was set in an arc ion plating device with a Ta-Ti alloy target as the evaporation source. Then, according to the coating conditions shown in Table 1, an intermediate layer made of a Ta-Ti alloy was formed on the surface of the substrate.

[0035] TIFF0007621071000001.tif56170

[0036] (Method (B)) A coating solution with a Ti:Ta=50:50 (molar ratio) was prepared by mixing 270 g / L TiCl4 solution, 125 g / L TaCl5 solution, and 10% hydrochloric acid solution. The prepared coating solution was applied to the surface of the pretreated substrate by brushing, and then dried at 60°C for 10 minutes. After baking at 520°C for 10 minutes in an air atmosphere in an electric muffle furnace, it was air-cooled to room temperature. The cycle from application of the coating solution to air-cooling was repeated until the coating amount was 1.3 g / m 2 (calculated by metal mass) was repeated to form an intermediate layer made of a Ta-Ti mixed oxide on the surface of the substrate.

[0037] <Manufacture of electrodes for oxygen generation> Example 1 [Formation of catalyst layer] A 1.65 mol / L tin (Sn) hydroxyacetochloride complex (SnHAC) solution was prepared according to the procedure described in WO 2005 / 014885. A 0.9 mol / L ruthenium (Ru) hydroxyacetochloride complex (RuHAC) solution was prepared according to the procedure described in WO 2010 / 055065. A 80 g / L Bi solution was prepared by dissolving BiCl3 in a 10% aqueous hydrochloric acid solution. A 130 g / L Mn solution was prepared by dissolving Mn(NO3)2·6H2O in a 10% aqueous acetic acid solution. A coating solution with a molar ratio of Ru:Mn:Sn:Bi=33:20:43:4 was prepared by mixing the RuHAC solution, Mn solution, SnHAC solution, Bi solution, and 10% aqueous acetic acid solution. The coating liquid prepared was applied by brushing onto the intermediate layer of the substrate having an intermediate layer formed on its surface by the above-mentioned method (A), and then dried at 60°C for 10 minutes. The substrate was baked in an electric muffle furnace in an air atmosphere at 520°C for 10 minutes, and then air-cooled to room temperature. The cycle from application of the coating liquid to air-cooling was repeated until the coating amount was 10 g / m2. 2 (calculated as the mass of Ru and Mn) was obtained, thereby forming a catalyst layer on the intermediate layer.

[0038] [Barrier layer formation] A coating solution with a molar ratio of Sn:Bi:Ru = 95:2:3 was prepared by mixing a RuHAC solution, a SnHAC solution, a Bi solution, and a 10% aqueous solution of acetic acid. The prepared coating solution was applied to the catalyst layer by brushing, and then dried at 60 °C for 10 minutes. After baking at 520 °C for 10 minutes in an air atmosphere in an electric muffle furnace, it was air-cooled to room temperature. The cycle from application of the coating solution to air-cooling was repeated until the coating amount was 3 g / m2. 2 (calculated by mass of Sn) was obtained, thereby forming a barrier layer on the catalyst layer, and an oxygen evolution electrode was obtained.

[0039] (Examples 2 to 11, Comparative Examples 1 to 3) An oxygen generating electrode was manufactured in the same manner as in Example 1 described above, except that each material was used to obtain the layer structure shown in Table 2, and firing and the like were performed under the conditions shown in Table 2. Note that post-baking was performed by holding the catalyst layer in an electric muffle furnace in an air atmosphere at 520°C for 1 hour after formation of the catalyst layer. In addition, the following tantalum (Ta) source, lanthanum (La) source, niobium (Nb) source, and iridium (Ir) source were used in the coating liquid for forming the catalyst layer. Tantalum (Ta) source: 125g / L TaCl5 solution Lanthanum (La) source: La(NO3)3 6H2O Niobium (Nb) source: Niobium(V) oxalate ammonium hydrate Iridium (Ir) source: 20.5% chloroiridic acid solution

[0040] TIFF0007621071000002.tif184170

[0041] <Evaluation> (Measurement of electrode potential) The electrode potential (V) of the produced oxygen generating electrode under oxygen generating conditions was measured by the method described below. The results are shown in Table 3. Current interruption method ·Electrolyte: 150g / L sulfuric acid aqueous solution ·Electrolyte temperature: 50℃ ·Working electrode area: 10mm×10mm Counter electrode: Zr plate (20mm x 70mm) ·Reference electrode: Mercurous sulfate (Hg / Hg2SO4)

[0042] TIFF0007621071000003.tif108170

[0043] (Durability test) A durability test of the oxygen generating electrode (catalyst layer) was carried out under the conditions shown below. ·Electrolyte: 150g / L sulfuric acid aqueous solution ·Electrolyte temperature: 40℃ ·Anode area: 20mm x 50mm ·Cathode: Zr plate (30mm x 70mm) Current density applied to the anode: 300A / m 2

[0044] The remaining amount of coating after a certain period of time was measured by XRF analysis, and the consumption of active metal elements (Ru, Mn, Ir) (g / m 2 The consumption rate (mg / m) of the active metal elements (Ru, Mn, Ir) was calculated from the calculated consumption amount and electrolysis time. 2 / h) was calculated. The results are shown in Table 4.

[0045] TIFF0007621071000004.tif107170 [Industrial Applicability]

[0046] The oxygen generating electrode of the present invention is used as an anode for electrowinning process of non-ferrous metals, or when the applied current density is less than 10 A / m 2 It is useful as an oxygen generating electrode used in the following electrolysis process. [Explanation of symbols]

[0047] 10, 20, 30, 40: Oxygen generation electrodes 2: Base material 4: Catalyst layer 6: Middle layer 8: Barrier layer

Claims

1. A substrate formed of titanium or a titanium alloy; a catalyst layer formed of a mixed metal oxide disposed on the substrate; The metal elements constituting the mixed metal oxide are composed of ruthenium, tin, and at least one metal element selected from the group consisting of bismuth, tantalum, lanthanum, niobium, and molybdenum, The oxygen generating electrode, wherein the content of ruthenium in the catalytic layer is 20 to 70 mol % based on the total metal elements in the catalytic layer.

2. An electrode for generating oxygen as described in claim 1, wherein the content of at least one metal element selected from the group consisting of bismuth, tantalum, lanthanum, niobium, and molybdenum in the catalytic layer is 2 to 20 mol % based on the total metal elements in the catalytic layer.

3. A substrate formed of titanium or a titanium alloy; a catalyst layer formed of a mixed metal oxide disposed on the substrate; The metal elements constituting the mixed metal oxide are composed of ruthenium, tin, manganese, and at least one metal element selected from the group consisting of bismuth, tantalum, lanthanum, niobium, and molybdenum, The oxygen generating electrode, wherein the content of ruthenium in the catalytic layer is 20 to 70 mol % based on the total metal elements in the catalytic layer.

4. 4. The oxygen generation electrode according to claim 1, further comprising an intermediate layer disposed between the substrate and the catalyst layer.

5. The oxygen generation electrode according to any one of claims 1 to 4, further comprising a barrier layer disposed on the catalyst layer.

6. The electrode for oxygen generation according to any one of claims 1 to 5, which is used as an anode for an electrowinning process of non-ferrous metals.

Citation Information

Patent Citations

  • Titanium anode containing ruthenium coating of high cerium content and its preparing method

    CN1900368A

  • JP1975026769A

  • Composite electrode and its production and use

    JP1986030690A

  • Electrode for electrolysis process

    JP2018524470A